Istibdal method for sustainable development: analyses of jurisprudence and implementation on waqf properties - Che Zuina Ismail,; Dalila Daud,; Amir Shaharuddin,; Al-Amirul Mukmin Al-Amin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Istibdal is a method for waqf properties development intended to solve underdevelopment problems of these properties. This paper intends to present an analysis of the relevant jurisprudence and how istibdal can be implemented specifically in waqf properties scenarios. This study used primary data sources through interviews to elicit information that shaped the implementation practice conducted. A literature review was also done to aid researchers to obtain secondary data on the waqf properties issues. Several law cases were reviewed to highlight important implementation issues addressed using istibdal method. This study shows how istibdal method is an innovation that offers a dynamic and comprehensive mechanism which facilitates the development of waqf properties in Malaysia and tailored with SDG11. It also shows how istibdal method can facilitates the development of waqf properties in Malaysia while achieving SDG goals. In line with the views of the majority sect in istibdal concept, it is a medium to sustain the waqf properties and lives. It turns out that Islamic Law has provided alternatives to address the problem of waqf property which is not liable to be converted to another property with a high prospect for development and public interests. However, it is done with integrity and to prevent conflicts and violations of waqf land. Thus, a law replaces the main principles of property law of conservation and sustainability of the assets. With the implementation of istibdal, these lands and other waqf properties have been successfully utilized, benefiting society.